Reading Diachronically: A New Reading of Book 36 of Cassius Dio’s Roman History - Lindholmer, Mads Ortving (Histos, 2018)
The recent revision of Cassius Dio (e.g. Lange and Madsen (2016b)) has underlined the complexity of his work and the independent interpretations therein, but Book 36 has been studied almost exclusively with a focus on the lex Gabinia (Coudry (2016)). In this article, I propose a new approach: to explore Book 36 diachronically from beginning to end and through this to demonstrate Dio’s skilful structuring of his narrative with the purpose of presenting political competition as the central destructive factor of the Late Republic. Dio presents this competition as an institutional problem, rather than a moral one, and his explanation of the decline of the Republic is thereby distinctive.